2020
DOI: 10.24093/awej/call6.13
|View full text |Cite
|
Sign up to set email alerts
|

Using Blended Learning to Support the Teaching of English as a Foreign Language

Abstract: The recent development in the field of technology in education has led to renewed interest in blending traditional methods of teaching with technology which might enhance language teaching and learning. The purpose of this paper is to review the literature concerning the strengths and weaknesses of blended learning as a technology-enhanced pedagogical tool that combines online and face-to-face instructional activities, on the development of English skills, inclusive of its use in the teaching of English as a F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…A further result is the students' perception that the Blackboard is a good and positive educational tool, as it gives pleasure in learning and helps to enhance the quality of learning. This reconciles with Nyabawa (2016) and Sheerah (2020), who concluded that the student academic performance is enhanced by frequent engagement on Blackboard, and with and Chen's et al (2020) argument that Blackboard Collaborate enhances students' online learning. Moreover, the results show that using the Blackboard platform gives students the feeling of being engaged in the classroom.…”
Section: Discussionsupporting
confidence: 77%
“…A further result is the students' perception that the Blackboard is a good and positive educational tool, as it gives pleasure in learning and helps to enhance the quality of learning. This reconciles with Nyabawa (2016) and Sheerah (2020), who concluded that the student academic performance is enhanced by frequent engagement on Blackboard, and with and Chen's et al (2020) argument that Blackboard Collaborate enhances students' online learning. Moreover, the results show that using the Blackboard platform gives students the feeling of being engaged in the classroom.…”
Section: Discussionsupporting
confidence: 77%
“…Importantly, their learning depends on the student characteristics described above in the discussion of the 3P model. The blended teaching model effectively activates the previously mentioned elements of students’ characteristics [ 55 ]. Teachers should assume not only a leading role in transmitting knowledge, but also in guiding, enlightening, and monitoring the teaching process, according to both Biggs’ 3P theory and the blended teaching model [ 23 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, in the environment of the blended teaching model, students’ English course experience was relatively good and they felt a higher sense of immersion and internal motivation [ 75 , 76 ]. For instance, blended teaching maximized the opportunity for learners to practice English listening using online resources freely at their convenience [ 55 ]. Moreover, the blended teaching model involved more extensive learning methods and channels than traditional learning, which proved more conducive to the development of students’ English skills and could arouse and activate positive emotions in learning preparation [ 77 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple benefits of blended learning contribute to language acquisition and affective values among students. Sheerah (2020) argues the result of blended learning in EFL classes as 1) it helps improve the digital literacy skills of lecturers and students; 2) students have two knowledge transformation spaces (offline and online); 3) it promotes increased student affective values (learning motivation, responsibility, discipline, and autonomy); 4) it provides current teaching materials; and 5) students can practice communicating in English with native English speakers from different countries. Pham (2023) states that teachers also benefit from online assessments and reports since they can monitor students' learning progress regularly and conveniently with more thorough information about each individual.…”
Section: Advantages Of Blended Learning In Esl/ Efl Classmentioning
confidence: 99%